Urinary neopterin in idiopathic retinal vasculitis. Issue 1 (1st January 2001) - Palmer, H E; Giovannoni, G; Stanford, M R; Wallace, G R; Graham, E M
Abstract : AIMS: To determine whether urinary neopterin:creatinine (UNC) ratios relate to disease activity in idiopathic retinal vasculitis (RV). METHODS: 18 patients with RV were prospectively recruited into a year long longitudinal study. Patients collected first morning urine samples on a weekly basis and on the same day completed a diary which documented their subjective view of RV activity and any concurrent infection. They were examined in clinic on a 6–8 weekly basis and an objective assessment was made of RV disease activity. 14 healthy controls collected urine samples in the same way. RESULTS: UNC ratios were significantly higher in patients than in controls (p=0.004, Mann-Whitney U test). UNC ratios were significantly higher when, according to their diaries, the patients had a subjective flare up of RV (p=0.001, Mann-Whitney U test). Subjective increased RV activity occurred more often when the patients had a concurrent infection (p<0.0001, χ 2 test). There was no significant difference in the UNC ratio between objective clinical relapse and non-relapse of RV. There was moderate agreement between the clinical assessment and patients' subjective impression of RV activity (κ=0.48). CONCLUSIONS: Higher neopterin levels reflect cell mediated disease that occurs in RV, but UNC ratios are not recommended as a means of monitoring clinical disease activity in RV.